2012
DOI: 10.1038/hr.2012.2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term ACE inhibition confers long-term protection against target organ damage

Abstract: Angiotensin converting enzyme (ACE) inhibitors reduce left ventricular (LV) hypertrophy and cardiovascular-renal fibrosis. Experimentally, changes in the LV and kidney persist even after cessation of treatment. The present study investigates whether brief ACE inhibition in spontaneously hypertensive rats (SHR) provides long-term protection against the LV and kidney damage induced by the nitric oxide synthase inhibitor N-x-nitro-L-arginine-methyl ester (L-NAME). SHR received the ACE inhibitor enalapril (n¼36) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 29 publications
(41 reference statements)
2
35
1
1
Order By: Relevance
“…, , Hale et al . ). Indeed, we have demonstrated that the hearts of SHR previously treated with an ACE inhibitor show a reduced proliferative, fibrotic and inflammatory response to short‐term nitric oxide synthase (NOS) inhibition (Hale et al .…”
mentioning
confidence: 97%
“…, , Hale et al . ). Indeed, we have demonstrated that the hearts of SHR previously treated with an ACE inhibitor show a reduced proliferative, fibrotic and inflammatory response to short‐term nitric oxide synthase (NOS) inhibition (Hale et al .…”
mentioning
confidence: 97%
“…ACEi are highly effective in controlling hypertension and reducing the risk of developing heart failure, left ventricular hypertrophy, insulin resistance, and microalbuminuria in diabetes [12,13,18,19,20]. Since ACE generates the vasoconstrictor peptide Ang II from Ang I and degrades the vasodilator bradykinin (BK), ACEi treatment improves vasodilatation by reducing Ang II and increasing BK.…”
Section: The Vasoconstrictive/pro-inflammatory Branchmentioning
confidence: 99%
“…Ang II would then bind to the Ang II type 1 receptor (AT1R) and induce signaling pathways that promote muscle constriction, salt and water retention, fibrosis, hypertrophy, and hyperplasia that underlie many metabolic diseases and poor cardiovascular and renal prognosis. Blockade of RAS can be exerted at multiple levels, via inhibition of renin, ACE, or AT1R signaling [6,7,8,9,10,11,12]. Efficient RAS blockers at all these levels have been developed and are currently in use to block overactivation of RAS and to offer protection from RAS-related metabolic diseases including diabetes [8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is suggested that RAS contributes to the atherosclerotic process through angiotensin Ⅱ, which acts as a proinflammatory mediator directly inducing atherosclerotic plaque development and heart remodeling and exacerbate endothelial dysfunction [81,82] . On the other hand, blockade of RAS can offer protection from RAS-related metabolic diseases including diabetes [83][84][85][86][87][88] . The statement by Demirci et al [72] is further enforced by the observation that the ACE gene may be a determinant of serum ACE levels, but it does not appear to confer susceptibility to essential hypertension [89] , since there are many factors that influence the genetic make-up of dicate that endothelial vasodilator capacity is impaired in PHTN [106] .…”
Section: Involvement Of the Renin-angiotensin System (Ras)mentioning
confidence: 99%